PENGARUH VARIABEL SOSIAL EKONOMI, DEMOGRAFIDAN IPK TERHADAP FINANCIAL LITERACY (Studi kasus terhadap mahasiswa Magister Manajemen di Universitas Udayana) - Mandala, IGN Narindra; Wiagustini, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.12.TAHUN 2017DO - 10.24843/EEB.2017.v06.i12.p07, 2017)
The low level of financial literacy amongst Indonesian people may concern to face ASEAN Economic Community (AEC). This study will analyze the sosio-economic factor(working period and income level), demographic factor (sex and marital status), and GPA factor of student of Master Management Program of Udayana University. The primary data is obtained using questionnaires, filled directly by the students concerned either directly or online. Analytical technique used in this study is partial least square analysis. The results shows that socioeconomic variable and GPA variable, are positively and significantly influence the financial literacy, measured by financial attitude, financial behavior and financial knowledge indicator. This findins are expected to contribute in the form of empirical and development of Financial Management Science refrence on socioeconomic, demographic and GPA influence the financial literacy, as well as to facilitate financial institutions when offering their products and services to Master of Management students at Unud.